YaBhg. Tun Arshad Ayub (Pro-Chancellor UiTM): Seri Setia Mahkota (S.S.M.) - UiTM, Arshad Ayub Graduate Business School (Arshad Ayub Graduate Business School, 2020)
Congratulations to YaBhg. Tun Arshad Ayub , Pro-Chancellor of Universiti Teknologi MARA, for being conferred the Seri Setia Mahkota (S.S.M.) on 17 August 2020.